Cardiac Fibrosis in Proteotoxic Cardiac Disease is Dependent Upon Myofibroblast TGF‐β Signaling. Issue 20 (16th October 2018) - Bhandary, Bidur; Meng, Qinghang; James, Jeanne; Osinska, Hanna; Gulick, James; Valiente‐Alandi, Iñigo; Sargent, Michelle A.; Bhuiyan, Md. Shenuarin; Blaxall, Burns C.; Molkentin, Jeffery D.; Robbins, Jeffrey
Abstract : Background: Transforming growth factor beta (TGF‐β) is an important cytokine in mediating the cardiac fibrosis that often accompanies pathogenic cardiac remodeling. Cardiomyocyte‐specific expression of a mutant αB‐crystallin (CryAB R 120G ), which causes human desmin‐related cardiomyopathy, results in significant cardiac fibrosis. During onset of fibrosis, fibroblasts are activated to the so‐called myofibroblast state and TGF‐β binding mediates an essential signaling pathway underlying this process. Here, we test the hypothesis that fibroblast‐based TGF‐β signaling can result in significant cardiac fibrosis in a disease model of cardiac proteotoxicity that has an exclusive cardiomyocyte‐based etiology. Methods and Results: Against the background of cardiomyocyte‐restricted expression of CryAB R 120G, we have partially ablated TGF‐β signaling in cardiac myofibroblasts to observe whether cardiac fibrosis is reduced despite the ongoing pathogenic stimulus of CryAB R 120G production. Transgenic CryAB R 120G mice were crossed with mice containing a floxed allele of TGF‐β receptor 2 ( Tgfbr2 f/f ). The double transgenic animals were subsequently crossed to another transgenic line in which Cre expression was driven from the periostin locus ( Postn ) so that Tgfbr2 would be ablated with myofibroblast conversion. Structural and functional assays were then used to determine whether general fibrosis was affected and cardiac function rescued in CryAB R 120G mice lacking Tgfbr2 in the myofibroblasts. Ablation of myofibroblast specific TGF‐β signaling led to decreased morbidity in a proteotoxic disease resulting from cardiomyocyte autonomous expression of CryAB R 120G . Cardiac fibrosis was decreased and hypertrophy was also significantly attenuated, with a significant improvement in survival probability over time, even though the primary proteotoxic insult continued. Conclusions: Myofibroblast‐targeted knockdown of Tgfbr2 signaling resulted in reduced fibrosis and improved cardiac function, leading to improved probability of survival.